А 11/x-2=11/2б 7/x+6 = -7/6

а) 11/x-2=11/2
б) 7/x+6 = -7/6

  • а) 11/х — 2 = 11/2
        11/х = 11/2 + 2
        11/х = 11/2 + 4/2 
        11/х = 15/2
         х = 11 : 15/2
         х = 11 * 2/15
         х = 22/15
         11 : 22/15 — 2 = 11/2
         11 * 15/22 — 2 = 11/2
         1/1 * 15/2 — 2 = 11/2
         15/2 — 2 = 11/2
         15/2 — 4/2 = 11/2
         11/2 = 11/2
    б)   7/х + 6 = — 7/6
          7/х = — 7/6 — 6
          7/х = — 7/6 — 36/6
          7/х = — 43/6
          х = 7 : (- 43/6)
          х = 7 * (- 6/43)
          х = — 42/43
          7 : (-42/43) + 6 = — 7/6
          7 * (- 43/42) + 6 = — 7/6
          1/1 * (- 43/6) + 6 = — 7/6
           — 43/6 + 6 = — 7/6
           — 43/6 + 36/6 = — 7/6
            — 7/6 = — 7/6